2016
DOI: 10.1016/j.foodchem.2016.01.140
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of microparticles of carotenoids from natural and synthetic sources for applications in food

Abstract: Carotenoids are susceptible to isomerization and oxidation upon exposure to oxygen, light and heat, which can result in loss of color, antioxidant activity, and vitamin activity. Microencapsulation helps retain carotenoid stability and promotes their release under specific conditions. Thus, the aim of the study was to encapsulate palm oil and β-carotene with chitosan/sodium tripolyphosphate or chitosan/carboxymethylcellulose and to assess the performance of these microparticles in food systems by analyzing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(61 citation statements)
references
References 29 publications
2
54
0
3
Order By: Relevance
“…They are found in plants, fungi, bacteria and algae and are present in many foods, for example, fruit, vegetables and fish (El‐Agamey et al ., ; Tapiero et al ., ). There are more than 600 carotenoids with natural structural variants which are divided into carotenes, xanthophylls and lycopene (Jomova and Valko, ; Rutz et al ., ). Only ~40 carotenoids are present in a typical human diet and about 20 carotenoids have been identified in human blood and tissues.…”
Section: Introductionmentioning
confidence: 97%
“…They are found in plants, fungi, bacteria and algae and are present in many foods, for example, fruit, vegetables and fish (El‐Agamey et al ., ; Tapiero et al ., ). There are more than 600 carotenoids with natural structural variants which are divided into carotenes, xanthophylls and lycopene (Jomova and Valko, ; Rutz et al ., ). Only ~40 carotenoids are present in a typical human diet and about 20 carotenoids have been identified in human blood and tissues.…”
Section: Introductionmentioning
confidence: 97%
“…Rutz, Borges, Zambiazi, da Rosa, and da Silva () evaluated the carotenoid release profile of microcapsules produced with chitosan/sodium tripolyphosphate and chitosan/carboxymethylcellulose as wall materials. The particles produced with chitosan/carboxymethylcellulose showed faster release in the gastric fluid (about 81%) and slower release in the intestinal fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted by Sousdaleff et al (2013), Zuanon et al (2013) and Rutz et al (2016) applied the lyophilization method to the encapsulation of different compounds and showed the acquisition of non-characteristic particles. They also showed that microparticle spheres were not formed, suggesting that, depending on the wall material, such conditions are not suitable for obtaining microcapsules, although the method has been commonly used.…”
Section: Resultsmentioning
confidence: 99%